Pengaruh Non-Performing Loans, Keputusan Investasi, dan Umur Perusahaan terhadap Tobin’s Q pada Perusahaan Sub-Sektor Perbankan Konvensional - Annisa Fairuz; Hadiyanto Wibowo; Edi Joko Setyadi; Rina Mudjiyanti (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
The COVID-19 pandemic has caused the economy in Indonesia to decline and credit risk to banks to increase. Risks that have increased in line with the increasing trend of the gross Non-Performing Loans ratio since 2020 compared to previous years, the Non-Performing Loans (NPL) ratio has a higher trend, thus encouraging the relative increase in Non-Performing Loans (NPL) in several sectors, including the banking sector. This study tests the effect of Non-Performing Loans (NPL), investment decisions, and company age on Tobin's Q on conventional banking sub-sector companies registered with the OJK during the Covid-19 pandemic (2020-2021 period). The study was conducted with multiple linear regression analysis. The population was all conventional banking companies registered with the OJK, while the research sample was 58, with the retrieval technique using random sampling. The result of this study is that investment decisions have a positive and significant influence on Tobin's Q. In contrast, Non-Performing Loans (NPL) and company age do not influence Tobin's Q.